Transforming the Bodleian: Introduction - Thomas, S (Walter de Gruyter GmbH, 2012)
The transformation of the Bodleian Libraries provides an example of how major libraries can meet twenty-first century challenges: in 2008 it was facing a failed system installation, a failed plan to cope with its storage needs and the threat of losing status as a repository suitable to house important manuscripts. Three years later it had a new state-of-the-art repository already holding 7 million items under full automated control, a new advanced library system, transformed reader spaces and the reconstruction of its major building well under way; This was achieved in record-breaking time without significant interruptions in service.